Characterization on mosaic glass excavated from Phu Khao Thong (Ranong), Thailand - K. Won-In (2018)
There were many glasses in forms of ornament and decorative objects found in Thailand for several hundred years. The mosaic glass used in this work was fragments that excavated at Phu Khao Thong proto-historic site in Ranong Province, southern area of Thailand which was a shred of glass looked-like Roman mosaic glass. Scanning electron microscope coupled with energy dispersive X-ray fluorescence spectroscopy (SEM-EDS) and proton induced X-ray emission spectroscopy (PIXE) were used to characterize the composition. Micro-beam X-ray fluorescence spectroscopy based on synchrotron radiation (μ-SRXRF) was also carried out to analyze its elemental composition and distribution. It was shown that the composition was similar to that of Roman mosaic glass which produced during the early 1st century A.D. The main composition was lead-based glass which colored from transition metals such as iron and copper. It demonstrated the long distance trade or exchange network of the ancient time. © 2013 The Authors.